2017
DOI: 10.1063/1.4999709
|View full text |Cite
|
Sign up to set email alerts
|

Critical size dependence of domain formation observed in coarse-grained simulations of bilayers composed of ternary lipid mixtures

Abstract: Model cellular membranes are known to form micro- and macroscale lipid domains dependent on molecular composition. The formation of macroscopic lipid domains by lipid mixtures has been the subject of many simulation investigations. We present a critical study of system size impact on lipid domain phase separation into liquid-ordered and liquid-disordered macroscale domains in ternary lipid mixtures. In the popular di-C16:0 PC:di-C18:2 PC:cholesterol at 35:35:30 ratio mixture, we find systems with a minimum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 110 publications
6
80
0
Order By: Relevance
“…Due to the slow diffusion of lipids and the microsecond timescale required to form lipid domains, most of MD studies involving simulations of lipid nanodomains employ coarsegrained models, 20,[86][87][88][89][90][91] although few studies using all-atom simulations can be found in the literature. 78,79,[92][93][94][95] Here, we retain the atomic-level resolution of Flipper-TR as its working mechanism may not be accurately represented by a coarsegrained model.…”
Section: Characterization Of Mechanosensitivity In Ternary Lipid Mixtmentioning
confidence: 99%
“…Due to the slow diffusion of lipids and the microsecond timescale required to form lipid domains, most of MD studies involving simulations of lipid nanodomains employ coarsegrained models, 20,[86][87][88][89][90][91] although few studies using all-atom simulations can be found in the literature. 78,79,[92][93][94][95] Here, we retain the atomic-level resolution of Flipper-TR as its working mechanism may not be accurately represented by a coarsegrained model.…”
Section: Characterization Of Mechanosensitivity In Ternary Lipid Mixtmentioning
confidence: 99%
“…An equilibrium average of one represents a perfect hexagonal packing and zero represents disordered packing. The phospholipid beads C2A/C2B and D2A/D2B (where A and B labels represent the two hydrophobic tails) in the phospholipid tail groups were used as points of reference with respect to the arbitrary vector 57 . All visualisations and analysis were implemented using a combination of VMD 58 , APLVoro 59 and MD-Analysis 60 , along with in-house scripts.…”
Section: Discussionmentioning
confidence: 99%
“…99 Increases in the exchange rate over those observed in this work would be necessary to support a transition to a phase separated state, which would likely require larger-scale simulations. 100,101 These simulations were performed at a very high concentration of AOT and water due to computational limitations on the system size. As our simulations were performed at compositions known to form RMs, we believe finite size effects are minimal.…”
Section: Discussionmentioning
confidence: 99%